2011
DOI: 10.1007/s12272-011-0903-8
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of a new series of benzimidazole derivatives

Abstract: Due to antimicrobial importance of benzimidazoles and hydrazones, some benzimidazole-hydrazone compounds were synthesized to screen their antimicrobial activity. Structures of the synthesized compounds were elucidated by (1)H-NMR, IR and ES-MS spectral data and elemental analysis. The synthesized benzimidazole-hydrazones exhibited very weak antibacterial activity. However, antifungal activity of some of the synthesized compounds was very notable against Candida species. The compounds displaying important antif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
30
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 33 publications
0
30
0
1
Order By: Relevance
“…1 Benomyl and methyl benzimidazol 2 yl carbamate (BBC and MBC), are benzimidazole fungicides widely used in China and worldwide on a large variety of crops to control plant pathogenic fungi [1]. How ever, many benzimidazole resistant pathogenic iso lates, e.g.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1 Benomyl and methyl benzimidazol 2 yl carbamate (BBC and MBC), are benzimidazole fungicides widely used in China and worldwide on a large variety of crops to control plant pathogenic fungi [1]. How ever, many benzimidazole resistant pathogenic iso lates, e.g.…”
mentioning
confidence: 99%
“…Stems form a worldwide need to adopt the practice of sustainable agriculture, using strategies that are environment friendly, less dependent on agricultural chemicals and less damaging to soil and water resources, there has been considerable interest in the utilization of sublethal doses of chemicals with biocontrol strains which are resistant to them, and the information on this kind of integrated control is accumulating more rapidly than on other combinations of control components [6]. 1 The article is published in the original.…”
mentioning
confidence: 99%
“…Furthermore, extensive literature search also suggested that only a limited efforts have been made to combine both these vital moieties in a single scaffold [1,28]. These findings boosted us to synthesis novel benzimidazole-hydrazone derivatives as antimicrobial agents.…”
Section: Introductionmentioning
confidence: 99%
“…Functional polymers with pendant antimicrobial groups have the advantage of non-leaching biocide effects without compromising their antimicrobial properties. Imidazolium and benzimidazolium compounds with N-substituted alkyl groups have demonstrated good antimicrobial activities (16,17). It has been reported that such polymers, prepared from imidazole derivatives, offer the advantage of good biocompatibility and bioactivity (18) .…”
Section: Introductionmentioning
confidence: 99%